Corrigendum to "Quantifying the uncertainty in simulating global tropospheric composition due to the variability in global emission estimates of Biogenic Volatile Organic Compounds" published in Atmos. Chem. Phys., 13, 2857–2891, 2013 - J. E. Williams; P. F. J. van Velthoven; C. A. M. Brenninkmeijer (Atmospheric Chemistry and Physics, 2013)
No abstract available.